Work Ethic of Bajo Women in Marine Product Processing on the Coast of Waburense Village, Central Buton - Taherong, Rosmawati; Cahyani, Waode Sitti (LPPM Institut Pendidikan Nusantara Global, 2025)
The Bajo people are a coastal community with a strong connection to the marine environment and a rich cultural heritage passed down through generations, encompassing value systems, gender-based role divisions, and traditional economic practices. Bajo women, known as ningkinda Bajo, play a central role in household economic activities such as fish processing, seaweed cultivation, and marketing despite having limited access to technology and formal education. This study aims to identify the work ethic of Bajo women and measure their resilience in managing marine resources in Waburense Village, Central Buton Regency. Using a qualitative descriptive method through field observations, in-depth interviews, and documentation, the study reveals that Bajo women operate under highly irregular working hours and face multidimensional challenges, including dual workloads, extreme environmental conditions, health risks, and limited access to resources. Their work ethic is reflected in their perseverance, physical endurance, adaptive strategies, and commitment to sustaining household and community economies. These burdens are compounded by structural factors such as poverty, low education levels, and insufficient policy intervention. The findings affirm that Bajo women are key actors in the socio ecological resilience of coastal communities. Therefore, inclusive and gender responsive empowerment policies are urgently needed to enhance their capacity, access to technology, skill training, and overall well being.